Development of APP about Cylindrical Gear Loaded Tooth Contact Analysis based on Industrial Internet Platform - Dake Liu; Bingyang Wei; Jiaqi Li; Xuekai Xie; Huaan Xiang (Jixie chuandong)
Compared with developed countries，China's industrial software development is still relatively backward，especially gear transmission design and analysis software. With the development of industrial internet and industrial APP，China's industrial software development will usher in a climax. The meshing stiffness and LTCA are very important for the dynamics analysis of gear transmission system. For this，based on SYSWARE.IDE industrial internet platform，the meshing information of tooth surface is analyzed by Ease-off difference tooth surface topology，and the cylindrical gear LTCA industrial APP is developed. By example，topological modified gradient diagram，contact line waterfall diagram，transmission error curve，time-varying meshing stiffness，change curve of load transmission error，load distribution state of tooth surface，load sharing ratio between teeth and other tooth surface information are output.